Application of image detection techniques in telecom operation and maintenance system - Bo FAN; Yun QIU; Lei SHEN (Dianxin kexue)
With the development of telecom industry,growing web service operations need more people to maintain the quality of the service.In the branch of telecom operation service,installation and maintenance service,the service quality is evaluated by human through assessing picture of construction site.The traditional way of evaluating quality of operation service brings low accuracy and high labor cost.In recent years,image recognition technology developed well with the deep learning raised,the related application field were broaden.If image recognition techniques were applied in telecom operation and maintenance system,the labor cost would be saved and the recognition accuracy would be improved.Several image recognition techniques were applied in installation quality assessment of telecom operation and maintenance system,and the performance and accuracy were analyzed.Based on analysis,a combining image recognition model was further proposed.The image recognition accuracy and efficiency of quality assessment was improved.